The Influence of Leadership Style and Interpersonal Communication On The Performance of The Public Relations Department In The Regional Police Force South Kalimantan - Sanjoyo Setyo Prabowo; Jamaluddin; Riduansyah Syafari (International Journal of Politic, Public Policy and Environmental Issues, 2022)
A leader's performance is essential, one of which is the performance of the Head of Public Relations at the South Kalimantan Regional Police. This study aimed to analyze the influence of leadership style and interpersonal communication on the Performance of the Public Relations section in the South Kalimantan Regional Police. This research method uses a quantitative approach with explanatory research or causal methods. The sample of study was 35 people with a total sampling technique, The Instrument was a questionnaire. The data analysis technique used multiple linear regression analysis, with a t-test and an f-test. The results showed that with a t or partial test there was a significant influence of leadership style on the Performance of the Public Relations Section in the South Kalimantan Regional Police. The partial test also showed that there was a significant influence of interpersonal communication on the performance of the Public Relations department in the South Kalimantan Regional Police. The simulation test results showed a significant influence of leadership style and interpersonal communication on the performance of the Public Relations section in the South Kalimantan Regional Police. The results of the r square test showed the influence of leadership style and interpersonal communication on the performance of the Public Relations section in the South Kalimantan Regional Police. The amount of which contributed the influence of independent variables to the dependent variables was 78.2% the remaining 21.8% was influenced by other variables not mentioned in this study.